Teaching Industrial Engineering in the Digital Age: A Reflective Study - Mardiani, Anindya (Journal of Sustainability Industrial Engineering and Management System, 2025)
The rapid advancement of digital technologies has prompted a paradigm shift in engineering education, particularly within the field of Industrial Engineering (IE), which inherently intersects with systems thinking and data-driven decision-making. This study aims to investigate how reflective teaching practices adapt to the digital transformation of IE education and to identify the pedagogical strategies that have emerged as effective in supporting student engagement and learning outcomes in digital environments. Employing a qualitative research design based on an integrative literature review, this research analyzed 52 peer-reviewed sources published between 2015 and 2024, drawing from databases such as Scopus, Web of Science, and ScienceDirect. Thematic analysis revealed four major insights: the transformation of pedagogical models through digital modalities such as flipped classrooms and simulation-based learning; the critical role of reflective teaching in enabling instructional adaptability; the persistent challenges related to inclusivity, digital inequity, and student motivation; and the need for sustainable institutional support to foster long-term pedagogical innovation. Findings indicate that reflective educators are more capable of integrating technological tools purposefully, responding to diverse student needs, and recalibrating their instructional approaches in dynamic learning contexts. Moreover, the study underscores the importance of embedding reflective practice into institutional development strategies and aligning them with inclusive digital pedagogy principles. This research contributes to the evolving discourse on engineering education in the digital age by offering actionable insights for educators, curriculum designers, and policymakers striving to build resilient, adaptive, and inclusive learning ecosystems in industrial engineering programs.